2021
DOI: 10.1161/hypertensionaha.121.17448
|View full text |Cite
|
Sign up to set email alerts
|

Effective Aspirin Treatment of Women at Risk for Preeclampsia Delays the Metabolic Clock of Gestation

Abstract: Preeclampsia, characterized by the onset of hypertension with significant proteinuria after 20 weeks’ gestation, is one of the leading causes of maternal and perinatal morbidity and mortality. Prophylactic low-dose aspirin treatment reduces the rate of preterm preeclampsia in high-risk women, but a significant proportion still develops preeclampsia. The mechanism of the prophylactic response is unknown. Here, the untargeted metabolomics analysis of 144 plasma samples from high-risk pregnant women before (11–13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Very recently, a study utilizing untargeted metabolomic analysis of plasma samples of aspirin/placebo-treated ASPRE trial participants has demonstrated that aspirin decreases significantly the metabolic clock-estimated gestational age. In addition, aspirin treatment partially reversed a wide range of metabolic changes over gestation, lending further support to our hypothesis that the benefit of aspirin treatment in preventing pre-eclampsia is mediated through decelerating the metabolic clock of gestation 6 .…”
Section: Replysupporting
confidence: 76%
“…Very recently, a study utilizing untargeted metabolomic analysis of plasma samples of aspirin/placebo-treated ASPRE trial participants has demonstrated that aspirin decreases significantly the metabolic clock-estimated gestational age. In addition, aspirin treatment partially reversed a wide range of metabolic changes over gestation, lending further support to our hypothesis that the benefit of aspirin treatment in preventing pre-eclampsia is mediated through decelerating the metabolic clock of gestation 6 .…”
Section: Replysupporting
confidence: 76%
“…Although aspirin is highly effective in preventing preterm pre-eclampsia and appears to defer disease onset by delaying placental aging 5,6 , the precise mechanism by which the disease is prevented remains poorly understood. Initial studies in the 1980s were triggered by evidence of increased placental thromboxane and reduced prostacyclin levels in pre-eclamptic pregnancies, and by the then-recent discovery that aspirin selectively inhibits thromboxane synthesis without affecting prostacyclin production 24 .…”
Section: Interpretation and Clinical Implicationsmentioning
confidence: 99%
“…However, while appropriate treatment of high-risk women with aspirin initiated in the first trimester is associated with a significant reduction in preterm pre-eclampsia risk, the exact mechanism by which aspirin prevents pre-eclampsia remains unclear. It has been shown that aspirin delays placental aging and disease onset 5,6 , and other theories include improvement in trophoblastic invasion, endothelial stabilization and reduction in inflammation [7][8][9] , but large human studies to support such theories are lacking. The effect of aspirin on biomarkers of pre-eclampsia is also poorly understood, and its knowledge may provide insights into the mechanism of action of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic analyses were conducted by Metabolon, Inc. using ultra-high-performance liquid chromatography/tandem mass spectrometry (UHPLC/MS/MS), as previously described [57]. Briefly, samples were analyzed through four different methods: (1) acidic positive ion conditions, chromatographically optimized for more hydrophilic compounds, (2) acidic positive ion conditions optimized for more hydrophobic compounds, (3) basic negative ion optimized conditions using a separate dedicated C18 column, and (4) negative ionization following elution from a HILIC column.…”
Section: Untargeted Metabolomicsmentioning
confidence: 99%